Pengaruh Capital Adequacy Ratio, Biaya Operasional Pendapatan Operasional, Return On Equity Dan Non Performing Loan terhadap Harga Sahamsub Sektor Perbankan yang masuk pada LQ-45 di Bursa Efek IndonesiaPeriode 2016 – 2020 - Erika Agustina (Universitas Batanghari Jambi, 2021)
This research aims to analyze fistly, how to analyze how the simultaneous influence of Capital Adequasi Ratio, Operating Expenses of Operating Income, Return on Equity and Non Performing Loan on Stock Prices on banks entered on the LQ-45 index during 2016 - 2020 . Secondly, how to analyze how the partially influence of Capital Adequasi Ratio, Operating Expenses of Operating Income, Return on Equity and Non Performing Loan on Stock Prices on banks entered on the LQ-45 index during 2016 – 2020. The research methodology is descriptive and quantitative analysis methods. Data used is secondary data. The population become object in this research is banking industry on Indonesia Stock Exchange period 2016 - 2020. Amount sample the used is the 5 (five) industry company and still stand up during period of perception and also publicized of year of 2016 - 2020 by Indonesian Stock Exchange. And the analysis multiple regression, hypotesis test so determinant coefficient F test and t test. The object of this research is banking industry on Indonesia Stock Exchange period 2016-2020. Sample of object is PT Bank Mandiri (Persero),Tbk (BMRI), PT Bank Negara Indonesia (Persero),Tbk (BBNI), PT Bank Rakyat Indonesia (Persero),Tbk (BBRI), PT Bank Tabungan Negara(Persero),Tbk (BBTN), PT Bank Central Asia,Tbk (BBCA). F test result, it is known that variabels Capital Adequasi Ratio, Operating Expenses of Operating Income, Return on Equity and Non Performing Loan simultaneously and significant effect on stock prices. Fcount bigger than Ftable (12.764 > 2.71) or comparing the not significant level of 0.05 then (0.000 < 0.05) then Ho is accepted and Ha rejected. Then multiple regression equations are Y = 1,145 + 4,123X1 - 0,013X2 - 1,178X3 - 1,721X4 + e. Based on the results of the t test, return on equity and non performing loan have significant effect on stock prices. Conclusion is the independent variable simultaneously have and significant effect on sotck prices and partially return on equity and non performing loan have significant effect on stock prices